2016
DOI: 10.1111/jog.13109
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of labor epidural analgesia among women aged over 40: A single‐institution retrospective study

Abstract: Our study showed that parturients aged ≥40 with LEA can expect similar LEA-associated labor outcomes to younger parturients with LEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The PH and mean of PCO2 and HCO3 were the same in both groups. Also, the incidence of CS in the EA group increased compared to the control group (13). The results of mentioned study are in direct agreement with our study, because in our study, the incidence of caesarean section in the epidural analgesia group was higher than that of spinal analgesia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The PH and mean of PCO2 and HCO3 were the same in both groups. Also, the incidence of CS in the EA group increased compared to the control group (13). The results of mentioned study are in direct agreement with our study, because in our study, the incidence of caesarean section in the epidural analgesia group was higher than that of spinal analgesia.…”
Section: Discussionsupporting
confidence: 92%
“…Okazaki and colleagues conducted a retrospective study to evaluate the effects of labor epidural analgesia on maternal and neonatal outcomes and found that the ABG parameters were not different between all groups (≥40 with labor epidural analgesia group; ≥40 without LEA group; <40 with LEA group) (13).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the incidence of operative delivery with intrapartum epidural analgesia was higher than that with no epidural analgesia . We did not study the difference between intrapartum epidural analgesia and no epidural analgesia.…”
Section: Discussionmentioning
confidence: 93%
“…The rate of pregnant women who request epidural analgesia during labor has been increasing annualy . In Japan, pregnant women's requests for intrapartum epidural analgesia have been increasing at a rate similar to that in other countries, as the number of older pregnant women (especially those over 40 years of age) has been rising …”
Section: Introductionmentioning
confidence: 99%
“…Epidural anesthesia and analgesia are commonly used for obstetric anesthesia. Epidural anesthesia is safe for use in cesarean sections, even in patients with cardiac diseases and severe pulmonary hypertension [4,7,[10][11][12][13][14][15][16]. Several methods, including wound infiltration with a local anesthetic and magnesium sulphate, wound infiltration with tramadol and levobupivacaine, a magnesium sulphate infusion for preemptive analgesia, a transverse abdominal plane block (TAPB) performed by adding dexamethasone to levobupivacaine, infiltration by placing a continuous catheter for a TAPB or the wound area, the administration of intrathecal and intravenous betamethasone, and the addition of dexmedetomidine to increase the efficacy of epidural anesthesia and analgesia have all been used to treat pain after a cesarean section [17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%